Sexual and reproductive health educational intervention for school teachers in district of Kalutara, Sri Lanka - R. Hettiarachchi; S. Sivayogan; S. A. P. Gnanissara (College of Community Physicians of Sri Lanka, 2007)
Introduction To plan and implement a Sexual and Reproductive Health (SRH) educational intervention for school teachers and evaluate the effectiveness of the intervention.     Methods An educational intervention was designed based on a situational analysis of existing SRH education in Sri Lankan schools. Intervention was carried out as four days teacher training workshop on SRH teaching for school teachers (thirty one) in the intervention group. Teachers in the control group (thirty) exposed to the pre-existing educational seminars conducted by the ministry of education at zonal level. After the intervention teachers in both intervention and control groups taught SRH lessons to grade nine students according to the existing school curriculum. Teaching skills were assessed using standard checklists. A quasi-experimental, equivalent control group design with pretest-posttest components was used to evaluate the effectiveness of the intervention. Sixty one teachers and 914 grade nine students aged 15-16yrs completed anonymous self reported pre-and post intervention questionnaires. Scores for baseline, first and second posttests were compared between intervention and control groups.   Results Results of the situational analysis showed that the ill prepared teacher is the main barrier for SRH education. Post intervention teaching skills were significantly improved in the intervention group (p-0.002). There was also a significant improvement in SRH knowledge and attitude among grade nine students (p < 0.05) in the intervention area after the intervention.   Conclusions Developing and conducting a · new educational intervention for SRH education based on situational analysis proved successful with regard to improved teaching skills as well as knowledge and attitudes among students.